Pengaruh Pengetahuan Akuntansi, Pendapatan Usaha Dan Pengalaman Usaha Terhadap Pengembangan Usaha (Studi Kasus Pelaku Usaha Mikro Kota Metro) - Sunarsih, Eli (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
This research aims to determine the influence of accounting knowledge, business income and business experience on business development (Case Study of Micro Business Actors in Metro City). The type of research used is quantitative research. The instrument used in this research is a questionnaire. Data analysis was carried out using multiple linear regression analysis. The research results show that Accounting Knowledge has a positive and significant influence on business development. Business experience has a positive and significant influence on business development. Business income has a positive and significant influence on business development. Accounting knowledge, business experience and business income have a positive and significant influence together on business development